Grid Computing 2008
DOI: 10.1007/978-0-387-09457-1_20
|View full text |Cite
|
Sign up to set email alerts
|

IANOS: An Intelligent Application Oriented Scheduling Framework For An HPCN Grid

Abstract: We present the architecture and implementation of IANOS middleware that is a result of integration of the Intelligent Scheduling Service into the VIOLA meta-scheduling environment. The goal of the new, integrated environment is to provide a general middleware infrastructure allowing optimal positioning and scheduling of HPC Grid applications. The scheduling algorithms used to calculate best-suited resources are based on an objective cost function that exploits information on the parameterization of application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
(1 reference statement)
1
7
0
Order By: Relevance
“…In speedup. This coincides with a similar observation made in [36] when the authors ran BLAST [37] jobs, in which they suggested that VM double caching caused the virtualized execution to be faster. …”
Section: Image Segmentationsupporting
confidence: 88%
See 1 more Smart Citation
“…In speedup. This coincides with a similar observation made in [36] when the authors ran BLAST [37] jobs, in which they suggested that VM double caching caused the virtualized execution to be faster. …”
Section: Image Segmentationsupporting
confidence: 88%
“…The effort described in [36] allows for cross-platform performance prediction of parallel applications. The prediction is achieved by combining the application's performance in a reference system and the relative performance between the two systems derived from a partial execution on the target platform.…”
Section: Ii21 General Performance Prediction Studiesmentioning
confidence: 99%
“…The IANOS resource broker implements all the models and features developed in this paper. More detailed on the implementation can be found in [8].…”
Section: Discussionmentioning
confidence: 99%
“…Gruber et al [15] present a similar approach in trying to model the execution time of an application on a particular set of resources for use in meta-scheduling decisions in a grid environment as part of the Ianos project. Their model includes several application-specific parameters and characteristics, which can be done with our model, but is not necessarily a prerequisite for good results.…”
Section: Related Workmentioning
confidence: 97%
“…Other works focus on system specific approaches [15]. In [16], the authors describe the use of the Dimemas tool to perform prediction of the execution behavior of message passing applications.…”
Section: Related Workmentioning
confidence: 99%